From Compact Discs to Streaming: A Comparison of Eras within the Brazilian Market - Seufitelli, Danilo B.; Oliveira, Gabriel P.; Silva, Mariana O.; Barbosa, Gabriel R. G.; Melo, Bruna C.; Botelho, Juliana E.; Melo-Gomes, Luiza de; Moro, Mirella M. (Revista Vórtex, 2022)
The music industry has undergone many changes in the last few decades, notably since vinyl, cassettes and compact discs faded away as streaming platforms took the world by storm. This Digital evolution has made huge volumes of data about music consumption available. Based on such data, we perform cross-era comparisons between Physical and Digital media within the music market in Brazil. First, we build artists' success time series to detect and characterize hot streak periods, defined as high-impact bursts that occur in sequence, in both eras. Then, we identify groups of artists with distinct success levels by applying a cluster analysis based on hot streaks' features. We find the same clusters for both Physical and Digital eras: Spike Hit Artists, Big Hit Artists, and Top Hit Artists. Our results reveal significant changes in the music industry dynamics over the years by identifying the core of each era.